The Impact of Adopting Digital Twins In Urban Development - Berawi, Mohammed Ali; Miraj, Perdana; Sari, Mustika (CSID Journal of Infrastructure Development, 2023)
The construction industry, which plays a pivotal role in urban development, has undergone a significant transformation in recent years. This transformation is largely marked by the rise of digitalization, a phenomenon fundamentally altering how we design, construct, and operate our urban environments. At the forefront of this paradigm shift is the notion of Digital Twins (DT), which entails a dynamic and virtual representation of tangible assets. Urban development has witnessed a growing adoption of this innovative approach to improve cities' infrastructure planning, construction, and management. Digital Twin enables real-time simulation and monitoring, enhancing performance and more informed decision-making. Therefore, implementing Digital Twin becomes crucial in developing sustainable, efficient, citizen-centric urban environments as cities expand and transform.